Language as sense and meaning in Gottlob Frege and Xavier Zubiri´S philosophy - Martínez Vásquez, Luis Arturo (2020)
This study aims to expose the notions of sign, meaning, reference and representation in the philosophical proposal of Friedrich Ludwig Gottlob Frege (1848-1925), as well as those of expression, signal, sign and meaning in the mature philosophy of Xavier Zubiri Apalategui (1898- 1983), with the aim of identifying relationships and differences, both in the starting points of his approaches to language, as well as in the concepts that articulate his proposals. In this way, it is concluded that Zubiri contributes both general aspects and terminological details to the philosophy of language today.